Analysis Of Particle Content In Kappaphyccus alvarezii Seaweed In The Waters Of Arakan Village Using Scan Electron Microscopy–Energy Dispersive X-ray Spectroscopy (SEM-EDX) - Tilaar, Sandra; Wullur, Stenly; Angkouw, Esther (Sam Ratulangi University, 2024)
Kappaphycus alvarezii seaweed is widely cultivated in Indonesia and has important economic value. Nevertheless, this seaweed is easily attacked by diseases. This study was to determine the ice-ice triggers in seaweed farming locations. This research study was conducted at Arakan Village, South Minahasa, North Sulawesi. We performed the bacteria isolation on the infected thallus of Kappaphycus alvarezii and found Staphylococcus arlettae caused the infection. Staphylococcus aureus used to be found on the skin and mucous membranes of healthy humans, while Staphylococcus epidermis inhabits only the skin of healthy humans. Approximately 30% of the normal healthy population was affected by Staphylococcus aureus as it asymptomatically colonizes human hosts. How this Staphylococcus arlettae (mainly found in pork farms) infected Kappaphycus alvarezii which is in a high salinity environment requires an in-depth study. We completed the experiment by using Scan Electron Microscopy–Energy Dispersive X-ray Spectroscopy (SEM-EDX), analysis on infected thallus Kappaphycus alvarezii, and a series of bacteria isolation to observe the morphology and the element contents of Staphylococcus arlettae bacteria has successfully attached to the surface of Kappaphycus alvarezii and caused an infection. This proves that environmental changes have stimulated pathogenic bacteria Staphylococcus arlettae in the area where Kappaphycus alvarezii is cultivated. The mechanism of biosorption by microbes that can live in environments that are contaminated with Pb metal is active uptake. This mechanism occurs simultaneously in line with the consumption of metal ions for the growth of microorganisms. Staphylococcus arlettae are resistant to heavy metals due to the ability to detoxify the influence of heavy metals in the presence of protein or granular material. From the results of the study using SEM-EDX of algae and bacteria Staphylococcus arlettae, it can be concluded that the content of the particle of metal in thallus triggers bacteria to live on the seaweed as an energy source. Keywords: Bacteria, disease, infection, Kappaphycus alvarezii, seaweed, Staphylococcus arlettae